(untitled) (Philosophy and Progress, 2021)
In this article, I propose a formal criterion that distinguishes between deductively valid arguments that do and do not beg the question. I define the concept of a Never-failing Minimally Competent Knower (NMCK) and suggest that an argument begs the question just in case it cannot possibly assist an NMCK in extending his or her knowledge. Philosophy and Progress, Vol#65-66-; No#1-2; Jan-Dec 2019 P 125-144